Tackling of Complicated Appendicitis by Laparoscopy: Is it Safe and Feasible? (Bangladesh Journal of Endosurgery, 2013)
Background: Laparoscopic appendectomy has been widely practiced for uncomplicated appendicitis. Various reports demonstrated its merits in reducing postoperative pain, analgesic requirement, incidence of wound infection, and hospital stay. The role of laparoscopy in management of complicated appendicitis remains undefined. Complicated appendicitis is associated with a significant risk of postoperative morbidity, making the value of the minimally invasive approach is superior.Methods: This is a retrospective study done in Chittagong Medical College Hospital and various private hospitals in Chittagong from January 2008 to June 2011. Sixty patients with complicated appendicitis included perforated appendicitis, gangrenous appendicitis, and appendicular abscess or lump found intra-operatively. The conversion rate, operative time, postoperative abdominal and wound infections, the return to oral intake, and the length of hospitalization were analysed. Laparoscopic appendectomy was done by three trocar techniques in all cases.Results: During the study period, 60 patients underwent laparoscopic appendectomy for complicated appendicitis. There were 35 patients with perforated appendicitis, 12 patients with gangrenous appendicitis, and 13 patients with early appendicular lump or abscess. The average operating time was 65 min. The average length of hospitalization was 3.2 (25) days. The postoperative narcotic analgesic requirement was minimal. Laparoscopy was converted to open surgery in two patients (3.33%). Four (6.6%) had postoperative complications (diarrhoea). Three patients developed (5%) wound (port) infection. There was no statistically significant difference in operative time (P 0.13). There was no mortality in the current series.Conclusions: Laparoscopic appendectomy is a safe and feasible treatment option in complicated appendicitis. It is advantageous than open surgery because of less wound infection, less morbidity, less hospital stay, early return to work, and not associated with increased risk of septic postoperative complications.DOI: http://dx.doi.org/10.11593/bje.2013.0102.0010Bangladesh Journal of Endosurgery Vol.1(2) May 2013: 11-14